IMPROVING THE ABILITY TO READ BEGINNING THROUGH PICTURE WORD CARD MEDIA IN CHILDREN - Endrawati, Endrawati; Ihlas, Ihlas; Retnoningsih, Retnoningsih (Waniambey: Journal of Islamic Education, 2024)
The problems that exist in children include students who are less enthusiastic in participating in learning, a rigid classroom environment, and students who do not concentrate when participating in learning activities, this is due to the media applied by the teacher is not interesting and fun, so it greatly impacts on the learning outcomes of grade I students related to beginning reading. The purpose of this study was to describe student learning outcomes using picture word cards, as well as to improve beginning reading skills. This research is called Classroom Action Research (CAR) and was conducted over two cycles with stages such as planning, implementation, observation, and reflection with a sample size of  31 students. The results of the findings show that in the pre-cycle activities that were completed as many as 7 students as much as 23% and those who did not complete 24 students as much as 77%, the increase in percentage in cycle 1 was 55%, while in cycle 2 it was 77% with details in cycle 1 18 students who were complete and 13 students were not complete, for cycle 2 24 students were complete and 7 students were not complete. From the results of this study, it has shown an increasing force in each cycle and the application of picture word cards has improved students' beginning reading skills.